2005
DOI: 10.1021/cg0497288
|View full text |Cite
|
Sign up to set email alerts
|

An In-Situ Synchrotron X-ray Diffraction Tomography Study of Crystallization and Preferred Crystal Orientation in a Stirred Reactor

Abstract: A new tomographic technique, based on synchrotron X-ray diffraction, has been used to chart polymorphic content and crystallite alignment inside a model pharmaceutical reactor. This reveals complex behavior according to crystallite shape/size characteristics; in particular, stirring induces pronounced crystal zonation marked by a boundary “alignment band” in which the crystallites adopt a “stand on edge” orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Experiments were conducted with pure phase and mixed a/b-polymorphs using 53-75 mm crystallites, stirred at a range of speeds. The previous results [5] show clear zonation of the bpolymorph; that is, the crystallites remain in the lower part of the vessel at the lowest stirring speeds. This material then rises up the vessel, becoming more diffuse, with an increase in stirring speed.…”
Section: Effect Of Stirring Speedmentioning
confidence: 58%
See 3 more Smart Citations
“…Experiments were conducted with pure phase and mixed a/b-polymorphs using 53-75 mm crystallites, stirred at a range of speeds. The previous results [5] show clear zonation of the bpolymorph; that is, the crystallites remain in the lower part of the vessel at the lowest stirring speeds. This material then rises up the vessel, becoming more diffuse, with an increase in stirring speed.…”
Section: Effect Of Stirring Speedmentioning
confidence: 58%
“…Data were collected at an angle of 4.61. Crystallite size and stirring speed experiments were conducted using suspensions of glutamic acid in ethanol; the a-form was obtained from BDH, and the b-form was re-crystallised from this form under appropriate conditions [5]. Different size ranges were obtained by sieving, and these were verified using particle size analysis.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two diffraction methods have been reported, namely X-ray diffraction (XRD) [78][79][80][81] and energy-dispersive X-ray diffraction tomography (EXDT) or alternatively called tomographic energy dispersive diffraction imaging (TEDDI) [82][83][84][85][86], where the former uses monochromatic X-ray while the latter makes use of polychromatic X-ray radiation. Despite the fact that diffraction itself does not give element-specific information, a recent study demonstrated its capability to monitor spatial distribution of specific chemical phases by recording diffraction and fluorescence signals simultaneously, and the distribution and composition of metal oxide species in CoMo/c-Al 2 O 3 catalyst have been elucidated [87].…”
Section: Synchrotron X-raymentioning
confidence: 99%